About the Heat Transfer Coefficient - Gareyev, А. А. (European Journal of Applied Sciences, 2022)
At present, oil production has reached such volumes that it poses ecological risks to the whole mother Earth. Being the backbone of the modern industry and the current economic strength of the mankind, oil production is toxic in terms of the global climate change and the negative effect on the natural habitat. Therefore, the analysis and identification of the ways to reduce the ecological impact of oil production has become a vital task for all nations throughout the world. One of the ways of reducing the adverse influence on the nature and the oil-bearing beds is the automation of oil production processes. The study of thermodynamic processes taking place in centrifugal pumps, lies at the core of automation of oil production and reduction of its ecological impact on the noosphere. The thermodynamics of movement of multi-component mixtures inside the centrifugal pump guide apparatuses is a poorly investigated phenomenon due to the lack of practical tasks. In multi-component mixtures the heat-transfer processes are non-standard, accompanied by phase transitions. In fact, this work is the first attempt to solve the said problem and deals with the deeper study of thermodynamic processes in centrifugal pump apparatuses. Knowing the processes of heat transfer and propagation in centrifugal pump apparatuses, it is possible to automate the whole process of centrifugal pump control without any complications in terms of its operation.